Identitas Budaya Islam Pada Novel 99 Cahaya Di Langit Eropa Karya Hanum Salsabiela Rais Dan Rangga Almahendra Kajian Antropologi Sastra Dan Implementasinya Sebagai Bahan Ajar Sastra Di Sma - Febriani, Lia, Imron Al-Ma'ruf, M.Hum, Dr. Nafron Hasyim (2016)
The purpose of this study there are four, namely :(1) describe the background of the socio-historical Hanum Salsabiela Rais and Rangga Almahendra as genetic factors; (2) describe a novel structure novel 99 Light in the Sky Europe works Hanum Salsabiela Rais and Rangga Almahendra; (3) describe a form of cultural identity of Islam novel 99 Light in the Sky Europe work Salsabiela Rais Hanum and Rangga Almahendra; (4) describe the implementation of the research results as teaching material in high school literature. This study uses qualitative descriptive method with fixed strategy. The object of this study is the work of Islamic cultural identity and Rangga Rais Hanum Salsabiela Almahendra on 99 novel Light in the Sky Europe. The data used in this study a word, a sentence, a paragraph in a novel 99 Light in the Sky Europe works Salsabiela Rais Hanum and Rangga Almahendra. Source of research data that have two primary data sources in the form of a novel 99 Light in the Sky Europe and secondary data sources include the journals, theses, and articles. Document collection techniques using literature techniques, see, and record. The data validation techniques using triangulation theory. Analysis of the data used is the model of semiotic readings, the readings heuristic and hermeneutic reading. The results of this study are four, namely (1) socio-historical works Salsabiela Rais Hanum and Rangga Almahendra nuance Islamic values by making Europe as the history of Islamic civilization; (2) a novel structure 99 Light in the Sky Europe covering themes, facts of the story in the form of plot, characterization, and background; (3) identity Islamic culture that is reflected in the novel 99 Light in the Sky Europe through seven cultural elements include languages such as Arabic calligraphy is on the plate Kufic. A system of public knowledge Europe uphold philosopher Cordoba named Averroes or Ibn Rushd. Social system or social organization as places of all religions coexist and be the transfer values of the harmony of life among religious. System life equipment and technology in Europe to save the Islamic civilization is maintained as lens technology. Livelihood systems of life of citizens of muslim settled in Vienna as did Natalie trade according to the teachings of Islam. The religious system in Europe's largest most religions that embraced Christianity and Catholicism. Art form of flamenco dance in Spain; (4) the implementation of the research results novel 99 Light in the Sky Europe as teaching material in high school literature include literary function, the learning function of literature, literary criteria for teaching materials, and learning steps literature. learning process adapted to the standard of competence number (7) and basic competences number (7.2) based curriculum applicable.